Variations in the Morphology of Human Lungs and its Clinical Implications - Jacob, Suja Mary; Venniyoor, Vaibhav; Pillay, Minnie (Journal of Morphological Sciences, 2019)
Objective To observe variations in the fissures, in the lobes, and in the hilar pattern of lungs and correlate these findings with clinical implications.Materials and Methods The present study was performed on random lung specimens available in the Department of Anatomy. A total of 96 lungs (47 right and 49 left) were studied for variations in the fissures and lobes, and 92 lungs (45 right and 47 left) for variations in the hilar pattern.Results Among the right-sided lungs, 70% presented incomplete horizontal fissure, 15% with absence of the horizontal fissure, and 51% with incomplete oblique fissure. Accessory fissures were also seen, but incomplete, and accounted for 17% of the total number of right lungs.Among the left-sided lungs, 62% presented incomplete oblique fissures, and 4% with absence of the oblique fissure. Accessory fissures accounted for 6% of the total number of left lungs.Regarding hilar pattern variations, 11% of the right-sided lungs showed > 2 bronchi, 69% showed > 2 pulmonary veins, and 37% showed > 1 pulmonary artery.Among the left-sided lungs, 57% showed > 1 bronchi, 21% showed > 2 pulmonary veins, and 17% showed > 1 pulmonary artery.Conclusion The field of pulmonary surgery is now highly advanced, with well-developed radiological and endoscopic techniques. Hence, a proper understanding and knowledge of these morphological variations of lung fissures and of the hilar pattern would be advantageous for surgeons, as well as for radiologists.
Keywords: accessory fissure; horizontal fissure; lung hilum; oblique fissure